Factors affecting the decision and attitude of teachers toward retirement. - De la Torre, Liza D. (1992.)
This study was undertaken to determine the factors and attitude of teachers towards retirement. The variables of the study were position levels and age brackets. The Attitude Measurement Scalling Procedure facilitates accurate and reliable instrument for both the reliability and the final attitude tests. Fifty (50) teachers from the municipality of Nva. Valencia were chosen to test the reliability of items. They were chosen accidentally. For the final set of tests, thirty five (35) percent of the total population of Jordan teachers were chosen. They were selected using the "Fish bowl" method by Fox. There were 110 teachers in the final tests. The Kruskal-Wallis One-Way Analysis of Variance by Rank or the H-test and frequency and percentage distribution facilitated in the analysis of data. With the use of the H-test, it showed that there is a significant difference among teachers of different age and position levels concerning their attitude towards retirement. Most teachers prefer early retirement and age 60 is the desired age for retirement. Moreover, the researcher was able to identify teachers's reasons for having positive and negative attitude towards retirement. Several factors too, were identified by the researcher that affect teachers' decision toward retirement. Factors were categorized physiologically, psychologically, socially, economically, and legally.
Thesis (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Teachers -- Retirement